Cestode larvae excite host neuronal circuits via glutamatergic signalling - Anja de Lange; Hayley Tomes; Joshua S Selfe; Ulrich Fabien Prodjinotho; Matthijs B Verhoog; Siddhartha Mahanty; Katherine Ann Smith; William Horsnell; Chummy Sikasunge; Clarissa Prazeres da Costa; Joseph V Raimondo (eLife, 2025)
Neurocysticercosis (NCC) is caused by infection of the brain by larvae of the parasitic cestode Taenia solium. It is the most prevalent parasitic infection of the central nervous system and one of the leading causes of adult-acquired epilepsy worldwide. However, little is known about how cestode larvae affect neurons directly. To address this, we used whole-cell patch-clamp electrophysiology and calcium imaging in rodent and human brain slices to identify direct effects of cestode larval products on neuronal activity. We found that both whole cyst homogenate and excretory/secretory products of cestode larvae have an acute excitatory effect on neurons, which can trigger seizure-like events in vitro. This effect was mediated by glutamate receptor activation but not by nicotinic acetylcholine receptors, acid-sensing ion channels, or Substance P. Glutamate-sensing fluorescent reporters (iGluSnFR) and amino acid assays revealed that the larval homogenate of the cestodes Taenia crassiceps and Taenia solium contained high concentrations of the amino acids glutamate and aspartate. Furthermore, we found that larvae of both species consistently produce and release these excitatory amino acids into their immediate environment. Our findings suggest that perturbations in glutamatergic signalling may play a role in seizure generation in NCC.